Rancang Bangun Alat Ekstraksi Ideal Menakar Kopi Berbasis Mikrokontroler ATMega2560 - Haidir, Asril Tito; Kurnia, Mega Tri; Saputro, Joko (Sistem Komputer dan Teknologi Intelegensi Artifisial (SIKOMTIA), 2023)
Coffee is a delightful and popular beverage with various flavor variations. The quality of coffee plays a pivotal role in influencing its taste and aroma. In an effort to enhance coffee quality, this research aims to design and implement a coffee extraction device based on microcontroller technology. Achieving the ideal coffee extraction quality involves factors such as time and temperature. Conventional coffee extraction devices have limitations in consistently controlling these factors. Therefore, the use of microcontrollers as a medium for coffee extraction promises more precise control. This study adopts a hardware and software development approach. Experimental tests, using baristas as samples, were conducted to assess the effectiveness of this device in measuring various types of coffee from Aceh, Toraja, and Flores. Parameters related to taste and aroma were evaluated to measure the extent to which the coffee extraction device could produce extractions that align with the expected flavor standards for coffee enthusiasts. This research successfully implemented an automated coffee measurement function with precision. Test results indicated that this device consistently produces coffee extractions with 98% consistency. In conclusion, this study illustrates the potential of microcontroller-based applications in enhancing the ideal coffee measurement quality. With more precise control, this device assists in creating optimal extraction conditions to achieve the desired flavor for coffee enthusiasts. This potential has a positive impact on elevating the quality of the coffee industry.